Profitability of Sharia Banking in Southeast Asia: ICSR, IPI and Zakat - Meita Trisna Dewi; Guntur Kusuma Wardana (International Journal of Economics Development Research (IJEDR), 2024)
Islamic banking has experienced rapid growth in Southeast Asia, driven by a large Muslim population and supportive government policies. However, challenges remain in implementing a standardized Islamic financial structure due to diverse cultural and economic landscapes. This study investigates the effects of Islamic Corporate Social Responsibility (ICSR), Islamicity Performance Index (IPI), and Zakat on the profitability of Islamic banks in Southeast Asia from 2019 to 2023. Using a sample of 12 Islamic banks, the study employs panel data regression analysis to examine the relationships between these variables. The findings reveal that ICSR and Zakat positively influence profitability, while the Profit-Sharing Ratio (PSR), the ratio of Islamic income to non-Islamic income, and the Equitable Distribution Ratio (EDR) do not have a significant effect. The study concludes that ICSR, PSR, EDR, Islamic income vs. non-Islamic income, and Zakat collectively influence profitability, contributing to the understanding of Islamic banking practices and their impact on financial performance in the region